2002
DOI: 10.1210/en.2002-220430
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Estrogen Receptor-α and cFos in Norepinephrine and Epinephrine Neurons of Young and Middle-Aged Rats during the Steroid-Induced Luteinizing Hormone Surge

Abstract: Norepinephrine (NE) and epinephrine are important stimulators of GnRH release during the preovulatory surge in female rats. Previous studies have shown that the catecholaminergic neurons are sensitive to estradiol and that NE release in the hypothalamus is decreased in middle-aged rats at the time when the estrous cycles become irregular and later cease to exist. The aims of the present study were to determine whether the NE and epinephrine neurons continue to express estrogen receptor (ER)-alpha in middle-age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Surprisingly, no estradiol receptors (ER␣ or ER␤) are found in the SVZ in mice (Mitra et al, 2003;Merchenthaler et al, 2004) although Isgor and Watson (2005) showed that Ki-67-immunoreactive cells of the SVZ expressed estrogen receptor alpha mRNA in rats. We thus suggest that estradiol most likely modulates cell proliferation by indirect pathways projecting to the SVZ such as dopamine ␤-hydroxylase (DBH) or tyrosine hydroxylase (TH) neurons which are estradiol-sensitive (Temel et al, 2002;Kishi et al, 2005) or by GPR30 which are membrane receptors binding estradiol (Bologa et al, 2006). Several reports suggested that GPR30 might be a G-protein coupled estrogen receptor mediating nongenomic effects of estradiol but its brain localization and its exact role remain still unknown (Micevych and Dominguez, 2009;).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, no estradiol receptors (ER␣ or ER␤) are found in the SVZ in mice (Mitra et al, 2003;Merchenthaler et al, 2004) although Isgor and Watson (2005) showed that Ki-67-immunoreactive cells of the SVZ expressed estrogen receptor alpha mRNA in rats. We thus suggest that estradiol most likely modulates cell proliferation by indirect pathways projecting to the SVZ such as dopamine ␤-hydroxylase (DBH) or tyrosine hydroxylase (TH) neurons which are estradiol-sensitive (Temel et al, 2002;Kishi et al, 2005) or by GPR30 which are membrane receptors binding estradiol (Bologa et al, 2006). Several reports suggested that GPR30 might be a G-protein coupled estrogen receptor mediating nongenomic effects of estradiol but its brain localization and its exact role remain still unknown (Micevych and Dominguez, 2009;).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to this, GnRH pulses and hence, LH secretion, are attenuated in middle-aged rats (8-12-month-old) (Rubin 2000). In addition, the central response to the steroidinduced LH peak in middle-aged rats is also attenuated in comparison to young rats (Gee et al 1984, Wise 1984, Rubin 2000, Temel et al 2002. Interestingly, oestrogens cause epigenetic modifications, switching the Kiss1 promoter to an active form, resulting in an increase in AVPV-specific Kiss1 gene expression (Tomikawa et al 2012).…”
Section: Oestrous Cycle Of Ageing Rats and Micementioning
confidence: 99%
“…DBH-ir fibers and terminals in these nuclei became thinner and had a decreased AOD after OVX, but these changes were attenuated following E 2 administration. It is known that catecholaminergic neurons are sensitive to E 2 , and norepinephrine release in the hypothalamus are decreased in middle-aged rats at the time when the estrous cycles become irregular and later cease to exist [31]. Estrogen has been shown to upregulate norepinephrine release in the mediobasal hypothalamus of OVX rhesus monkeys [32], which is in accordance with our results and indicates that low estrogen was mainly responsible for the decrease of DBH-ir fibers and terminals in the POAH after OVX.…”
Section: Discussionmentioning
confidence: 99%